2014
DOI: 10.5489/cuaj.1989
|View full text |Cite
|
Sign up to set email alerts
|

Intravesical treatment with highly-concentrated hyaluronic acid and chondroitin sulphate in patients with recurrent urinary tract infections: Results from a multicentre survey

Abstract: Introduction: We assess the effectiveness of intravesical instillation of hyaluronic acid (HA) and chondroitin sulphate (CS) as a non-antibiotic treatment option for prophylaxis of recurrent urinary tract infections (UTIs) in female patients. Methods: This was a retrospective cohort study involving 7 European institutions. We included patients with recurrent UTIs who received intravesical instillations of Ialuril (IBSA International) (50 mL HA 1.6% and CS 2% solution) between January 2010 and March 2012. Medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 27 publications
3
30
0
3
Order By: Relevance
“…Some of these studies have been more extensive and have included two randomised trials as well. All these studies have demonstrated a reduction in the mean number of UTI recurrences and an increase in the recurrence-free interval [19][20][21][22]. Thus, our results have been congruent with the outcomes reported in the literature.…”
Section: Discussionsupporting
confidence: 91%
“…Some of these studies have been more extensive and have included two randomised trials as well. All these studies have demonstrated a reduction in the mean number of UTI recurrences and an increase in the recurrence-free interval [19][20][21][22]. Thus, our results have been congruent with the outcomes reported in the literature.…”
Section: Discussionsupporting
confidence: 91%
“…Glycosaminoglycan instillations when compared clinically to placebo and antibiotics have been found to be linked to fewer episodes of UTI recurrence in women and longer periods between infections 28, 29, 30. Hence, these agents appear protective against UTIs.…”
Section: Introductionmentioning
confidence: 99%
“…As in the Damiano study, tolerability of the Ialuril formulation was good, with no serious adverse events reported. Recently Cicione and colleagues [Cicione et al 2014] assessed the effectiveness of intravesical instillation of HA and CS as a nonantibiotic treatment option for the prophylaxis of recurrent UTIs in female patients at seven European institutions. They used intravesical instillations of 50 ml HA 1.6% and CS 2% solution in 157 women with recurrent UTIs.…”
Section: Clinical Evidencementioning
confidence: 99%